IMPROVING LISTENING SKILLS OF ELEMENTARY SCHOOL STUDENTS THROUGH MUSIC AND SONGS - Ismatova Shakhnoza; Sodiqova Zamira; Ne’matullayeva Sevinch; Olimjonov Asqar (Western European Studies, 2024)
Music and song activities can enhance and develop young learners’ listening ability. Listening is a primary language skill, which needs to be developed before the other language skills and particularly the speaking ability. It is an indispensable condition for developing a person’s second language abilities. A sample group of Grade 4 classes in a research project included 30 English additional language learners. One grade 4 classes were selected, 15 pupils were being the experimental and the other 15 were being the control group. Over a month, the experimental group was exposed to and received planned music and song activities daily. A significant difference in the means between the control and the experimental groups was recorded during a re-test done on all learners of the two classes. The experimental group performed well in their listening abilities in English as a second language. This finding has important teaching implications for ESL
Keywords: music; song activities; young learners; control group